Graded heterojunction of perovskite/dopant-free polymeric hole-transport layer for efficient and stable metal halide perovskite devices. (December 2020) - Li, Zijia; Park, Jaehong; Park, Hansol; Lee, Jongmin; Kang, Yeongkwon; Ahn, Tae Kyu; Kim, Bong-Gi; Park, Hui Joon
Abstract: Solution-processed polycrystalline perovskite films possess numerous imperfections in their surface and grain-boundary, limiting their solar cell performance and stability. To attain a full thermodynamic potential from the device along with high stability, an efficient passivation strategy that can suppress those imperfections, inducing a trap-assisted charge recombination and a defect-initiated crystal decomposition, is needed. Herein, we demonstrate a perovskite/dopant-free polymer hole-transport material (HTM) graded heterojunction (GHJ), maximizing their intermolecular interactions that can passivate under-coordinated lead cations in perovskite and immobilize its volatile organic cations by forming Lewis-adducts and hydrogen bonds. For this purpose, a series of polymer HTMs, containing defect-healable and cross-linkable functional units, are newly designed. By composing a GHJ structure, it is confirmed the perovskite crystallinity increases with reduced trap-density, enhancing built-in potential of the solar cell device and thus decreasing carrier recombination, and its heat-, water-, and light-resistibility are enhanced. Consequently, superior optoelectronic properties, providing efficiencies of 22.1% (0.096 cm 2 ) and 20.0% (1 cm 2 ) with a V oc of 1.22 V having only 0.37 V V oc loss, and stability, preserving 92% of the initial efficiency after 500 h of light-illumination (AM 1.5G 100 mWcm −2 without UV-cut) in ambient air without encapsulation, are attained with the GHJ n-i-p devices. Graphical abstract: Perovskite/dopant-free polymer hole-transport material (HTM) graded heterojunction (GHJ), maximizing their intermolecular interactions that can passivate under-coordinated lead cations in perovskite and immobilize its volatile organic cations by forming Lewis-adducts and hydrogen bonds, is demonstrated. For this purpose, a series of polymer HTMs are newly designed. Consequently, superior properties, providing efficiencies of 22.1% (0.096 cm 2 ) and 20.0% (1 cm 2 ) with a V oc of 1.22 V having only 0.37 V V oc loss, and stability, preserving 92% of the initial efficiency after 500 h of light-illumination without UV-cut in ambient air without encapsulation, are attained. Image 1 Highlights: Dopant-free polymer hole-transport materials (HTMs), having defect-healable and crosslinkable functional groups, are newly designed. A graded heterojunction (GHJ) structure between perovskite and dopant-free HTM, on which additional HTM does not need to be added, is demonstrated. GHJ maximizes intermolecular interaction between HTM and perovskite that can passivate under-coordinated lead cations in perovskite and immobilize its volatile organic cations by forming Lewis-adducts and hydrogen bonds. Superior properties, providing efficiencies of 22.1% (0.096 cm 2 ) and 20.0% (1 cm 2 ) with a V oc of 1.22 V having only 0.37 V V oc loss, are achieved. Long-term stability, preserving 92% of the initial efficiency after 500 h of light-illumination without UV-cut in ambient air without encapsulation, is attained.